2011
DOI: 10.1155/2011/465281
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Enriched and Nonenriched Enrollment Randomized Withdrawal Trials of Opioids for Chronic Noncancer Pain

Abstract: EERW trial designs appear not to bias the results of efficacy, but they underestimate the adverse effects. The present updated meta- analysis shows that weak and strong opioids are effective for CNCP of both nociceptive and neuropathic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 70 publications
3
91
0
Order By: Relevance
“…e6 In addition, the AAN, in its Choosing Wisely campaign, recommends not using opioids or butalbital for treatment of migraine, except as a last resort. 13 Furlan et al, 14 in a recent review of RCT of opioids for CNCP, concluded that the overall effectiveness of opioids for pain was modest, and that the effect on function was small. Most of the RCT were shorter than 4 weeks, and none was longer than a few months.…”
Section: Evidence For Efficacy and Effectivenessmentioning
confidence: 99%
“…e6 In addition, the AAN, in its Choosing Wisely campaign, recommends not using opioids or butalbital for treatment of migraine, except as a last resort. 13 Furlan et al, 14 in a recent review of RCT of opioids for CNCP, concluded that the overall effectiveness of opioids for pain was modest, and that the effect on function was small. Most of the RCT were shorter than 4 weeks, and none was longer than a few months.…”
Section: Evidence For Efficacy and Effectivenessmentioning
confidence: 99%
“…Interestingly, the little endogenous critical literature on enriched enrollment takes issue not with its limited external validity, but with the claims to improved internal validity. Several authors have noted that the use of a run-in phase prior to randomization, which familiarizes all participants with a drug's effects, presents a risk for unblinding (Leber and Davis, 1998;Staud and Price, 2008a, b;Furlan et al, 2011;Hall and Kaptchuk, 2013). In addition, a recent meta-analysis comparing enriched with non-enriched trials for opioids in chronic non-cancer pain found that contrary to its rationale, EERW studies did not appear to produce stronger measures of efficacy, but tended to underestimate adverse events, which, as we will explore below, has a particular salience for studies of chronic pain treatments (Furlan et al, 2011;Quessy, 2011).…”
Section: "Unsettling Circularity"mentioning
confidence: 99%
“…1 Opioids have shown only small to moderate benefits in relieving nociceptive and neuropathic pain and improving function. 9 For neuropathic pain, they are considered second-line to alternative therapies, including antidepressants and anticonvulsants, in available guidelines. 10 Opioids are not indicated for migraine or tension headaches or for patients with irritable bowel syndrome.…”
Section: Is For Indicationmentioning
confidence: 99%